Health Literacy and Online Health Information Processing: Unraveling the Underlying Mechanisms. (1st August 2016) - Meppelink, Corine S.; Smit, Edith G.; Diviani, Nicola; Van Weert, Julia C. M.
Abstract : The usefulness of the Internet as a health information source largely depends on the receiver's health literacy. This study investigates the mechanisms through which health literacy affects information recall and website attitudes. Using 2 independent surveys addressing different Dutch health websites ( N  = 423 and N  = 395), we tested the mediating role of cognitive load, imagination ease, and website involvement. The results showed that the influence of health literacy on information recall and website attitudes was mediated by cognitive load and imagination ease but only marginally by website involvement. Thus, to improve recall and attitudes among people with lower health literacy, online health communication should consist of information that is not cognitively demanding and that is easy to imagine.